Overcoming barriers and uncertainties to investing in forested watershed restoration in California - Ayompe, Lacour Mody; Padilla, Lace; Eriksson, Max; Egoh, Benis N.; Bales, Roger C. (Frontiers in Forests and Global Change, 2025)
IntroductionLarge-scale investments in restoring California’s forested watersheds are imperative for conserving biodiversity, enhancing water quality, and mitigating the future impacts of climate change. This study explores the underlying incentives, major challenges, and potential strategies associated with such investments.MethodsAn online survey was administered to 43 experts in the field to gather their insights on forest watershed restoration investments. The collected responses were then analyzed using a combination of confirmatory factor analysis and regression analysis to elucidate patterns and relationships.ResultsThe analysis revealed that key environmental outcomes, such as reducing wildfire risks and protecting water supplies, are the principal motivators driving investment. At the same time, significant barriers emerged, including high costs, limited workforce capacity, and insufficient trust among stakeholders. The study also identified a series of effective strategies to overcome these obstacles, such as repositioning forest restoration as an infrastructure investment and clearly demonstrating its ecological, social, and economic benefits.DiscussionOverall, the findings underscore the need for more flexible funding frameworks, enhanced stakeholder engagement, and improved data infrastructures. By addressing these elements, policymakers and practitioners can pave the way for more resilient and sustainable forested-watershed ecosystems in California.